Study Of Patient's Opinions in A Diagnostic Centre to Measure Patient Satisfaction - Kanan T Desai; Richa Nahar; R K Bansal (Medsci Publications, 2012)
Objective: Patient satisfaction surveys guide for betterment of service as per people's needs and this study aims to understand the process involved. Method: Quantitative study done in a diagnostic centre with structured questionnaire from January to March, 2011. 66 home visit, 84 collection centre and 14 lab to lab feedback forms were filled. Statistical analysis was done with SPSS 15. Results: At collection centers, 100% customers got immediate attention from reception. 95.24% patients had smiling interaction from lab staff. Only 50% patients were given probable estimate of bill. 7.14% patients were not informed about probable report collection time. None of the 84 patients had to wait for report collection. In home visit 6.06% patients reported delayed service. In lab to lab feedback 42.86% felt report turn around time was average. Conclusion: Efforts should be made to improve the lacunas, so that customer retention and repeat customer proportion increases.